The Students’ Mathematical Problem Solving Skills in Solving HOTS Problems - Alif Septriansyah; M. Imamuddin; Devi Apriyanti; Martini Dwi Pelitawaty (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
Problem-solving skills have a vital role in students' daily lives. This research aims to describe the students' problem-solving skills in solving HOTS problems. This research is a descriptive study. The research subjects used were 33 eleventh-grade students at one of the senior high schools in Musi Banyuasin, South Sumatera. Problem-solving test with the HOTS problems level was used as a data collection instrument. The results of this study depicted that the students have medium problem-solving skills. The students' problem-solving skills are inconsistent in solving HOTS questions. In understanding the problem stage, students have been able to write down the information obtained from questions, but some have not been able to write down complete and ideal information. While in determining plans and strategies stage, students have been able to make mathematical models based on the information obtained in the previous stage. The students are weak in solving problems stage because students are still not complete in solving problems according to the commands of the questions. The students also have weak in rechecking stage. So, teachers must optimize students' problem-solving skills. The teachers need to optimize students' problem-solving skills through exercises in solving HOTS problems using Polya's steps.